Dampak Kinerja Keuangan Akibat Praktik Keberlanjutan Lingkungan - Rahayu, Ruci Arizanda; Setyarini, Yulia; Andini, Nadia Trisna; Inayah, Nur Lailiyatul (Institut Teknologi dan Bisnis Yadika, 2025)
This study aims to examine the effect of environmental sustainability performance on corporate financial performance. Environmental sustainability performance in this study is assessed using the variables of green accounting, environmental costs, corporate social responsibility, and green intellectual capital, with the research objects being mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected using a purposive sampling method, resulting in 39 companies. Multiple regression analysis was employed as the analytical method. The findings indicate that green accounting and environmental costs have a negative effect on the financial performance of mining companies. Meanwhile, corporate social responsibility and green intellectual capital do not have a significant effect on the financial performance of mining companies.